2014
DOI: 10.1007/s11274-014-1684-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculation method on the determination of decontamination efficacy against Bacillus spores

Abstract: Decontamination studies investigating the effectiveness of products and processes for the inactivation of Bacillus species spores have traditionally utilized metering viable spores in a liquid suspension onto test materials (coupons). The current study addresses the representativeness of studies using this type of inoculation method compared to when coupons are dosed with a metered amount of aerosolized spores. The understanding of this comparability is important in order to assess the representativeness of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Further, it is likely that the inoculation method could have a significant effect on inactivation rates. This was demonstrated in a study investigating chemical decontaminants, in which Ryan et al [ 37 ] showed that inactivation rates were indeed affected by the spore inoculation method.…”
Section: Resultsmentioning
confidence: 85%
“…Further, it is likely that the inoculation method could have a significant effect on inactivation rates. This was demonstrated in a study investigating chemical decontaminants, in which Ryan et al [ 37 ] showed that inactivation rates were indeed affected by the spore inoculation method.…”
Section: Resultsmentioning
confidence: 85%
“…Ryan et al . () found that the spore inoculation method did affect decontamination efficacy results, but the effect varied by material and decontaminant. Nevertheless, our B. anthracis Ames and B. atrophaeus decontamination efficacy results agree well with Rogers et al .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, other studies have noted that differences in decontamination efficacy can been attributed to inoculation method. [42] Because liquid spores were deposited in ten discrete spots of 100 μL across a coupon in a predictable pattern rather than evenly distributed, it is possible that: (1) the location of contamination was known and therefore unintentionally targeted during the decontamination procedure; (2) physical removal of contaminants is more efficient when the liquid inoculum is dried into small, discrete locations rather than deposited as dry particles over the entire coupon surface; and (3) the actual amount of inoculated surface area was significantly smaller for liquid tests (the area under ten small droplets), and thus decontamination procedures had a much higher probability of treating 100% of the contaminated area. For example, if a small amount of coupon surface area was inadvertently neglected during the decontamination treatment, the impact on viable spore recovery could be much greater for the tests with dry inoculums.…”
Section: Discussionmentioning
confidence: 99%